Continuous glucose monitoring for type 1 diabetes. (2nd February 2023) - Gordon, Charlotte
Abstract : Continuous glucose monitoring (CGM) is now a standard of care technology, which enables people living with type 1 diabetes to quickly monitor and manage their glucose levels without frequent, painful, finger-prick testing. This article will provide an overview of CGM technologies, including the most common types of devices, the data generated and information regarding access to these devices via NHS funding, alongside guidance for CGM use in clinical practice. Diabetes technologies are developing at pace, and so practice nurses will increasingly encounter people using CGM. Continuous glucose monitoring is now available to all those living with type 1 diabetes. Charlotte Gordon provides an overview of the technology for nurses working in general practice